2004
DOI: 10.1097/01.inf.0000128778.54105.06
|View full text |Cite
|
Sign up to set email alerts
|

Influence of School Closure on the Incidence of Viral Respiratory Diseases Among Children and on Health Care Utilization

Abstract: We evaluated the effect of school closure on the occurrence of respiratory infection among children ages 6-12 years and its impact on health care services. During this period, there were significant decreases in the diagnoses of respiratory infections (42%), visits to physician (28%) and emergency departments (28%) and medication purchases (35%). The present study provides quantitative data to support school closure during an influenza pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
121
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 15 publications
5
121
0
1
Order By: Relevance
“…Had the school holidays not taken place, it is reasonable to suppose that there would have been a single large wave of influenza cases. School holidays have also been linked to a reduction in incidence of ILI in France [20] and Israel [22]. A review of school closures in relation to influenza can be found in Cauchemez et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…Had the school holidays not taken place, it is reasonable to suppose that there would have been a single large wave of influenza cases. School holidays have also been linked to a reduction in incidence of ILI in France [20] and Israel [22]. A review of school closures in relation to influenza can be found in Cauchemez et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to school closure, the risk of transmission may be reduced further by giving prophylactic treatment with antivirals like oseltamivir that are active against influenza viruses. However, it is difficult to predict how effective these measures will be during a real outbreak and the evidence is limited [3,4]. Even though children stay away from school, they may still meet in large groups outside school and the effectiveness of antiviral prophylaxis is dependent on compliance with taking the medication.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a large study of military recruits found that a structured top-down program of hand-washing at least five times daily nearly halved the incidence of acute respiratory illnesses, while recruits who washed hands less frequently reported more episodes of acute respiratory illnesses (OR 1.5, 95% CI 1.2 to 1.8) [11]. Interestingly, promoting hand-washing and using soap to wash hands were both associated with significantly reduced school absenteeism [12]. Teachers generally agree that a hand-washing program is easy to implement among primary students: step (1) wet hands, (2) lather fingers, (3) lather palms and backs of hands, (4) rinse, and (5) dry with a clean towel [13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an Israeli study of 186,094 children (between six and twelve years of age) reported temporary, preventative school closures resulted in a (a) 42% decreased morbidity from respiratory tract infections, (b) 28% decrease in visits to physicians and/or emergency department, and (c) 35% reduction in the purchase of medications [12].…”
Section: Discussionmentioning
confidence: 99%